(untitled) - Angel, George G. (New York, 2010)
This accessible guide bridges the gap between being a project manager and becoming a globally recognized Project Management Professional (PMP). Covering the latest PMP exam content from the Project Management Institute (PMI), the book explains PMI's worldwide standard methods, nine knowledge areas, and 42 processes. You'll learn proven strategies for improving project efficiency and effectiveness, balancing constraints, communicating timely and accurate project status, and successfully bringing a project to completion. A real-world case study that's followed throughout the book provides helpful examples, checklists, and proven project results.
Keywords: Project management,Quản trị dự án